Spectral Characteristics of Plastic Debris in the Beach: Case Study of Makassar Coastal Area - Ahmad Faizal; Shinta Werorilangi; Wasir Samad (Faculty of Geography, Universitas Gadjah Mada, 2020)
Plastic debris becomes a global problem that threatens the coastal ecosystems, and the supralittoral area (beach) turns to be a place for plastic debris to accumulate. Data from the United Nations (UN) states that Indonesia is the second plastic debris contributor in world waters. This study aimed to examine the spectral characteristics of plastic debris accumulated on the beach. The data was collected from the coast of Makassar at 3 different stations: Jenneberang River estuary, Losari Beach and Tallo River estuary. The spectral sample was measured using a 4000 A spectroradiometer that works on a wavelength spectrum of 340 - 1040 nm. The results showed that the optimum value for plastic debris identification in the coastal area at low tide (dry sand) is 450-670 nm and at high tide (wet sand) is 450-950 nm. This value will be a reference in the remote sensing method, especially multispectral classification in mapping plastic debris found in coastal areas, and will be one solution to effectively mapping plastic debris.